ANALISIS PERAN STAKEHOLDERS DALAM PENGELOLAAN BUMDES DI KABUPATEN SEMARANG (STUDI KASUS BUMDES MITRA SEJAHTERA DESA MENDONGAN KECAMATAN SUMOWONO) - Anggie Ayuni Nurfakhirah; R. Slamet Santoso; Retna Hanani (Journal of Public Policy and Management Review, 2021)
ABSTRACT The role of stakeholders is one of the important things in achieving policy success. Village-Owned Enterprises (BUMDes) as a business entity that becomes a forum for village governments to build the village economy requires the participation and involvement of stakeholders in managing each business unit. Mendongan Village is one of the villages that need attention in its management because of the lack of support and contributions from related stakeholders. This research was conducted to determine the role of stakeholders by mapping stakeholders in the management of Mitra Sejahtera Village-Owned Enterprises (BUMDes) in Mendongan Village, Sumowono District, Semarang Regency. The approach used is descriptive qualitative with observation data collection techniques, interviews, documentation, and literature study. The results of this study prove that there are roles of stakeholders which are grouped into four, namely policy makers, coordinators, facilitators, and implementers. The results of the role analysis show that the application of the principles of cooperation, participation, independence, justice, and equality is still not good enough. The results of stakeholder mapping using the Value Orientation Mapping show that the stakeholders involved are the Mendongan Village Government, the Management / Head of the Mitra Sejahtera BUMDes in Mendongan Village, the Mendongan Village community and staff of the Semarang Regency Community Service and Village Empowerment, Semarang City Government and Semarang Regency Regional Government